Semi-rigid thoracoscopic punch biopsy using a hybrid knife with a high-pressure water jet for the diagnosis of pleural effusions - Yin, Yan; Eberhardt, Ralf; Wang, Xiao-bo; Wang, Qiu-yue; Kang, Jian; Herth, Felix; Hou, Gang (Respiration, 2016)
Semi-rigid thoracoscopy is an important technique in the definitive diagnosis of pleural diseases with high diagnostic sensitivity and specificity. Obtaining adequate samples from thickened pleura is the most important limitation of semi-rigid thoracoscopy with a standard flexible forceps (SFF) compared with rigid thoracoscopy, especially in patients with mesothelioma or benign fibrothorax. Developing a convenient, efficient and safe biopsy technique to obtain sufficient samples from such patients is a key topic in semi-rigid thoracoscopy. The hybrid knife (HK) is an innovative design fusing high-pressure water injection and a conventional diathermic knife that can allow for the safe resection of a larger lesion during gastrointestinal endoscopic dissection. Here, we describe 3 patients with unexplained pleural effusion who underwent pleural biopsy using an HK to investigate the potential use of the HK as a new pleural biopsy device in semi-rigid thoracoscopy when pleural lesions are difficult to biopsy using an SFF. The biopsies were obtained successfully by HK, and the diagnosis followed. The sizes of the biopsies collected by HK are larger than those collected by SFF. No complications were observed. Electrocautery biopsy using an HK during semi-rigid thoracoscopy has great potential for diagnosing consistent abnormal pleuras, which are difficult to biopsy with an SFF.
Gesehen am 30.09.2021